Opportunistic infections in patients treated with immunotherapy for cancer. Issue 1 (18th June 2014) - Kyi, Chrisann; Hellmann, Matthew D; Wolchok, Jedd D; Chapman, Paul B; Postow, Michael A
Abstract : Immunomodulatory antibodies that enhance the immune system to fight cancer are revolutionizing the treatment of patients with an expanding variety of malignancies. There is a unique spectrum of side effects associated with immunomodulatory antibodies, termed immune-related adverse events (irAEs), which include colitis and hepatitis among others. The treatment of refractory or severe irAEs can occasionally require significant immunosuppression, involving steroids or tumor necrosis factor-alpha antagonists, placing these patients at risk for infections. We present the first reported case to our knowledge of an opportunistic infection in a patient treated with an immunomodulatory antibody. As the use of immunomodulatory antibodies expands and more patients develop irAEs that require treatment with immunosuppression, recognition of the potential for opportunistic infections in this emerging patient population will be critical. Prospective trials are needed to define the optimal immunosuppressive management of irAEs and determine whether prophylactic antiviral, antibacterial, or antifungal therapies are beneficial in this unique population.